Evaluation of the Sanitation Clinic Program on Environment-Based Diseases Between Tanjung Pinang Health Center and Paal V Health Center in Jambi City - Auffa Nabila; Arnild Augina Mekarisce; Fajrina Hidayati; Adelina Fitri; Andree Aulia Rahmat; Nour Abdeljawad; Carey Louise Arroyo (Tecno Scientifica Publishing, 2025)
Public Health Centers with a high incidence of environment-based diseases showed that the percentage of sanitation clinic program implementation was lower compared to those with a low incidence of environment-based diseases. This study aimed to evaluate the outcomes of sanitation clinic activities at the Tanjung Pinang Public Health Center and the Paal V Public Health Center in Jambi City in 2024. This study employed a qualitative method conducted from May to June 2024. Data were obtained from 11 informants selected through purposive sampling techniques. Data collection was carried out through in-depth interviews, observations, and document analysis. The sanitation personnel at both Public Health Centers had not received sanitation clinic training. There was no budget allocated for sanitation clinic activities at either health center. The facilities at Paal V were less complete than those at Tanjung Pinang. The method used at Tanjung Pinang followed the Indonesian Ministry of Health Regulation No. 13 of 2015, while Paal V referred to the Ministry of Health guidelines from 2001. Both health centers had planning activities. Tanjung Pinang implemented counseling, environmental inspections, and environmental interventions, while Paal V only provided counseling. The output for counseling, environmental inspections, and environmental interventions was higher at Tanjung Pinang compared to Paal V. Tanjung Pinang is expected to remain consistent in implementing the sanitation clinic program. Paal V is encouraged to improve its counseling, environmental inspections, and environmental interventions.